Recognising barriers to implementation of Blue-Green infrastructure: a Newcastle case study - O'Donnell, Emily C.; Lamond, Jessica E.; Thorne, Colin R. (Taylor & Francis, 2017)
There is a recognised need for a fundamental change in how the UK manages urban water and flood risk in response to increasingly frequent rainfall events coupled with planned urban expansion. Approaches centred on ‘living with and making space for water’ are increasingly adopted internationally. Nonetheless, widespread implementation of Blue-Green infrastructure (BGI) is currently hampered by barriers that impede uptake and innovation. We investigate the barriers to implementation of BGI in Newcastle, UK, through a series of semi-structured interviews with professional stakeholders. We identify and categorise 17 types of barrier and identify targeted strategies to overcome the dominant barriers. We recommend promotion of BGI’s capacity to meet the objectives of multiple organisations and Local Authority departments, in addition to managing urban water. We conclude that strong business cases, supported by monetised evidence of benefits, and collaborative, inter-agency working could advance implementation of BGI within the current flood risk management legislation.